Interplay of Different Contextual Motivations and Their Implications for Exercise Motivation - Gonzàlez-Cutre, David (Asist Group, 2011)
The aim of this study was to analyze the interaction between different contextual motivations and exercise motivation. The sample consisted of 449 exercisers aged between 16 and 53 years. Questionnaires were used to measure the satisfaction of basic psychological needs, self-determined motivation and the autotelic experience during exercise. The level of self-determined motivation regarding health, leisure and interpersonal relationships was also measured. The results of the structural equation modeling demonstrated that basic psychological needs and self-determined motivations about health and leisure positively predicted the self-determined motivation to exercise. Moreover, the self-determined motivation to exercise positively predicted the autotelic experience. The model was invariant across age, although some gender differences were found. Specifically, the self-determined motivation towards health in men did not significantly predict the self-determined motivation to exercise. These results represent to evaluate the role that other contextual motivations play in exercise motivation.